ENDOCRINE RESPONSE TO AN ULTRA-MARATHON IN PRE- AND POST-MENOPAUSAL WOMEN - Copeland, J.L.; Verzosa, M.L.S. (Biology of Sport, 2014)
Ultra-endurance competitions are becoming increasingly popular but there is limited research on female participants. The purpose of this study was to examine changes in estrogen and the IGF-I system in women after an ultra-marathon. Six pairs of pre- and post- menopausal women were matched for race finish times;mean finish time was 20 hours. Blood samples were drawn 24 hours before the race, at the finish, and 24 hours into recovery. Samples were analysed for estradiol, total IGF-I, IGFBP-1, and intact IGFBP-3. There was a significant increase in estradiol following the race in both groups (P<0.05). Total IGF-I decreased after the race (P<0.01) and remained lower in recovery. IGFBP-1 increased after the race (P<0.001) but returned to pre-race levels after 24 hours, while intact IGFBP-3 was significantly lower post-race and in recovery (P<0.001). Postmenopausal women had significantly lower estradiol at baseline, but there were no other group differences. These results demonstrate that among recreational female runners, an ultra-marathon is associated with IGF system changes that are consistent with an energy-deficient, catabolic state. Further research is needed to confirm the effect of these endocrine changes on health and performance